2015
DOI: 10.4103/2347-5625.167232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an education program on knowledge, self-care behavior and handwashing competence on prevention of febrile neutropenia among breast cancer patients receiving Doxorubicin and Cyclophosphamide in Chemotherapy Day Centre

Abstract: Objective:To evaluate the efficacy of an education program on the prevention of febrile neutropenia (FN) among breast cancer patients receiving AC regimen.Methods:Randomized controlled trial with the repeated-measures design was conducted in a Chemotherapy Day Centre of an acute hospital in Hong Kong. Twenty-five subjects in the intervention group received an individual education session followed by three follow-up sessions and routine care. Twenty-four subjects in the control group received routine care. Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Consistent with a recent review on mobile apps for individuals with chronic diseases [ 14 ], this study identified that participants were engaged and empowered when using the app. An increase in the activation levels may encourage health-related behaviors, such as increasing physical activity, dietary behaviors, and medication adherence [ 39 , 40 ], as well as support closer monitoring of their disease symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a recent review on mobile apps for individuals with chronic diseases [ 14 ], this study identified that participants were engaged and empowered when using the app. An increase in the activation levels may encourage health-related behaviors, such as increasing physical activity, dietary behaviors, and medication adherence [ 39 , 40 ], as well as support closer monitoring of their disease symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fertel & Naljayan () found that the use of digital media strengthened hand‐washing techniques. Mak & Ching (), in their study with people who had cancer, found that group training offered to the patients resulted in positive changes regarding hand‐washing behaviour. Piatt et al () demonstrated that diabetes self‐management training based on the chronic care model improved the clinical and behavioural outcomes of individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing intervention increases the mothers’ awareness and knowledge about HPV vaccine which promotes their positive perception about the vaccine. This is correlated with the studies of Mark and Yin Ching, Umezulike et al ., and Ezeanolue et al [ 22 24 36 ] The concept of prevention can be well understood if given by health personnel, like nurses. Therefore, increase in knowledge about HPV and HPV vaccine is an important way to increase vaccination rates among mothers of the adolescents in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done among women in Hong Kong, education program on prevention of febrile neuropathy had a significant favorable effect on the intervention group. [ 22 ] Chang et al . [ 23 ] reported that in China effect of an educational intervention on HPV in knowledge and vaccine attitudes among urban employed women and female undergraduate increased HPV knowledge scores in the intervention group.…”
Section: Introductionmentioning
confidence: 99%